Answer:
1st fraction =
2/6*3/2
2nd fraction =
3/6*2/2
Step-by-step explanation:
X+4x-y5 is the wrong answer
Answer:
The correct answer is D. -2,592, -15,552, -93,312
Step-by-step explanation:
Each of the terms is the previous term multiplied by 6. You can find this by taking any term and dividing it by the one before it. The answer will always be 6.
-72/-12 = 6
-12/-2 = 6
So, in order to find the next 3, we take the last term and multiply it by 6.
-432 * 6 = -2,592
-2,592 * 6 = -15,552
-15,552 * 6 = -93,312
Answer:
associative! property! of! addition!
Step-by-step explanation:
we change the order of the addends but the sum doesn't change
Answer:
Step-by-step explanation:
6.7